Approaches to vaccination of adults against pneumococcal disease in different countries of the world - A. S. Korovkin; Yu. I. Obukhov; E. N. Syatchikhina (Журнал инфектологии, 2024)
Various pneumococcal vaccines are available worldwide, differing in the range of serotypes coverage and type of vaccine, which determine different mechanisms of action and postvaccinal immunity. Vaccination  against  pneumococcal infection is recommended for both children and adults. Based on information from public sources, we analyzed recommendations for vaccination of adult patients in various countries. The information was summarized in the main blocks: the availability of government funding and vaccination programs for all persons depending on age; availability of government funding and vaccination programs for all patients with risk factors; availability of vaccination recommendations depending on age and risk factors, not funded by the state. The collected data also was analyzed according to vaccination schedules and recommended types of pneumococcal vaccines. In fact, few countries have included vaccination of adults in their preventive vaccination schedules. Pneumococcal disease vaccination in adults is primarily the prerogative of economically developed countries. Currently, there is a clear transition from mono-vaccination with the polysaccharide pneumococcal vaccine PPV23 and combined vaccination regimens with a 13or 15-valent pneumococcal conjugate vaccine with revaccination with PPV23 to monovaccination with a 20-valent pneumococcal conjugate vaccine. Taking into account the spectrum of detected pneumococcal serotypes and molecular epidemiology data available in our country, the use of PCV20 can be considered justified.